Happy birthday, Molly! : a springtime story - Tripp, Valerie, 1951-; Backes, Nick; Skeen, Keith (Middleton, WI : Pleasant Co., 2000)
When an English girl comes to stay at Molly's during World War II, she and Molly learn to bridge their differences and ultimately enjoy a wonderful, mutual birthday party.
"American girl."
"Book 4"--Cover.
4.0
3-6
Keywords: Friendship -- Fiction; World War, 1939-1945 -- United States -- Fiction; Historical fiction; Friendship -- Fiction; World War, 1939-1945 -- United States -- Fiction; Historical fiction